2005
DOI: 10.1190/1.2052471
|View full text |Cite
|
Sign up to set email alerts
|

Least-squares joint imaging of multiples and primaries

Abstract: INTRODUCTIONMy Least-squares Joint Imaging of Multiples and Primaries (LSJIMP) algorithm (Brown, 2003b) separates pegleg multiples and primaries. LSJIMP computes separate images of the peglegs and primaries, and then uses the mutual consistency of the images to discriminate against unwanted noise types in each image. The images must be consistent in two respects: kinematics and amplitudes. A companion paper (Brown, 2003a) paper addresses the amplitude issue. In this paper, I address the kinematics. Kinematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Even with the added complication of regularization and use of two-pass, one-way methods, it is still faster to make an image in this way than to use reverse-time methods. An added advantage of the ability to separate images made with singly, doubly, and triply scattered waves is that these separate images can be used to identify artifacts from crosstalk (as discussed in detail by Brown and Guitton [2005]), allowing an interpreter to assess the likely artifacts in each image separately. By using an image, rather than including the interface directly in the velocity model, one can still use discontinuous or poorly imaged structures to estimate and thus exploit multiply scattered waves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even with the added complication of regularization and use of two-pass, one-way methods, it is still faster to make an image in this way than to use reverse-time methods. An added advantage of the ability to separate images made with singly, doubly, and triply scattered waves is that these separate images can be used to identify artifacts from crosstalk (as discussed in detail by Brown and Guitton [2005]), allowing an interpreter to assess the likely artifacts in each image separately. By using an image, rather than including the interface directly in the velocity model, one can still use discontinuous or poorly imaged structures to estimate and thus exploit multiply scattered waves.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to methods discussed by Brown and Guitton (2005), imaging with multiply scattered waves requires the separation of these multiples from primaries. Although a method such as that suggested by Brown and Guitton would likely result in a cleaner image with fewer artifacts, we have found that much simpler procedures are adequate, in particular for doubly scattered waves.…”
Section: Summary Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Youn and Zhou (2001) devised a prestack depth migration method that used a model-based estimate of the internal multiples. Data-driven methods for imaging using internal multiples include least squares migration (Brown and Guitton, 2005), interferometric imaging (Jiang et al, 2005), one-way wave equation migration (Malcolm et al, 2009), full wavefield migration (Berkhout, 2012), RTM for internal multiples (Liu et al, 2011;Fleury, 2013) and generalized internal multiple imaging (Zuberi and Alkhalifah, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This motivates us to take a look at the data-domain, where, in principle, we can include multiples by using the full wave-equation to model the data. It should be mentioned that some attempts have been made to use multiples in migration (see, for example, Youn & Zhou, 2001;Brown & Guitton, 2005;Jiang et al, 2007). Data-domain methods come in various shapes and sizes, however, we will focus on waveform inversion.…”
Section: Introductionmentioning
confidence: 99%